The relationship between primitive reflex profile and development of vestibular maturity in early school years - Erzsébet Stephens-Sarlós (Exercise and Quality of Life)
Previous research indicates that vestibular perception is related to muscle tone regulation. Muscle tone influences auditory and visual perception. Research findings suggest that the functioning of primitive reflexes affects the maturation and condition of the vestibular organ. The goal of the study is to examine whether the primitive reflex profile can be influenced by appropriate exercises and whether inhibition of persistent primitive reflexes affects vestibular functions. The sample consisted of 506 children aged 5–8 years (237 boys and 269 girls). In kindergartens and schools, 443 participants performed reflex inhibition exercises 3–5 times a week for 7 months. A control group of 63 individuals attended only regular PE lessons. Input and output results were compared using the Mann-Whitney test, and effect sizes were calculated. Input primitive reflex profile and vestibular maturity: not significant. Effect size: primitive reflex profile: 0.109; vestibular maturity: 0.052. Output: primitive reflex profile: p <0.001; vestibular maturity: p <0.001. Effect size: primitive reflex profile: 0.572; vestibular maturity: 0.306. The results obtained with appropriate non-parametric measurements show that children participating in the intervention achieved statistically significantly higher scores in all tested variables of primitive reflex profile and vestibular maturity compared to the control group. The children in the intervention group showed significant improvement in both primitive reflex profile and vestibular maturity: p <0.001; effect size: primitive reflex profile: 0.714; effect size: vestibular maturity: 0.664; while there was no significant improvement in the control group: effect size primitive reflex profile: 0.01; vestibular maturity: 0.06. We found a strong, significant correlation between the inhibition of primitive reflexes and vestibular maturity: r=0.000; rho (ρ)=0.000. Based on this study we recommend incorporating these exercises into physical education for 5–8-year-old children.